National Action plan for Agriculture GHG Inventory Improvement Haiti - Stevens, Luanne (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
The CARICOM AgREADY project, funded by the Green Climate Fund, aims to position Caribbean agriculture as part of the solution for addressing climate change. The project targets nine countries to improve policies, capacities, frameworks, methods and institutional arrangements for the agriculture sector. The objectives are to improve the enabling conditions for climate action, increase the number of evidenced-based projects for investment, and disseminate best practices for building climate-resilience through institutional capacity building and coordination. Additionally, the project seeks to develop a National Action Plan to improve the agriculture Greenhouse Gas Management inventory by assessing the status of the inventory, identifying areas for improvement, developing actions, and prioritizing them.